Identifying core social relationship factors in the psychological recovery of subclinical depression: An expert consensus study using the Fuzzy Delphi method - Ibrahim, Taufiq; Ayub, Norzihan; Ading, Carmella E (Journal of Islamic, Social, Economics and Development, 2026)
Social relationships are a key determinant of psychological well-being, influencing emotional regulation, stress management, coping capacity, and overall life satisfaction across the lifespan. Supportive connections with family, friends, peers, and the community provide emotional comfort and play an important role in fostering hope, meaning, and adaptive functioning during psychological recovery. Recovery-oriented mental health perspectives emphasise that recovery is inherently relational, relying on supportive social environments rather than solely on internal psychological processes. In this context, subclinical depression defined by depressive symptoms that do not meet criteria for Major Depressive Disorder remains clinically significant, as it is linked to impaired functioning, reduced quality of life, emotional distress, and social withdrawal. These symptoms can progressively weaken interpersonal relationships, further limiting social support and hindering psychological recovery. This study aims to identify and prioritize the core social relationship factors in the psychological recovery of subclinical depression, based on the consensus of counseling psychology practitioners using the Fuzzy Delphi method. Study concludes that psychological recovery in individuals with subclinical depression is predominantly shaped by the quality of social relationships rather than their structural characteristics. Through iterative expert consensus and defuzzification, the availability of emotional support emerged as the highest-priority factor, reflecting strong convergence among experts regarding its central role in recovery.